Firing angle effect in fully controlled single phase bridge rectifier / Mohd Arman Adnan and Wan Azlan Wan Hashim - Adnan, Mohd Arman; Wan Hashim, Wan Azlan (2005)
Rectifier is used to convert AC (alternating current) to DC (direct current). It is a important part of constructing power supply. Alternating current (AC) flowed in one way, then the other way. continually reversing direction. An AC voltage is continually changing between positive and negative. The rate of changing direction is called the frequency of the AC and it is measured in hertz (Hz) which is the number of forwards-backwards cycles per second. An AC supply is suitable for powering some devices such as lamps and heaters but almost all electronics circuits require steady DC supply. Direct Current (DC) always flows in the same direction, but it may increase and decrease. Our project is all about how to control the tiring angle in rectifier. One way how to control it’s by using thyristor. We cannot control the firing angle if we use the diode. It is an advantage if we using the thyristor because it can controlled the firing angle. The advantage of full wave bridge is it can conduct in both, positive and negative cycle. We choose Matlab Simulink to show the waveform that we get from the circuit that we design. We have design the rectifier circuit with and without the capacitor. The capacitor is behaves like a filter that make the output waveform become smoother than not using capacitor. This rectifier is designed in basic design to provide ease constructing, troubleshooting, low power and cost.